FAMILY NURSING CARE FOR Mr. S ON THE PATIENT TYPE II DIABETES MELLITUS WITH A FOCUS ON ACTION FOOT EXERCISES TO LOWER BLOOD SUGAR BLOOD AT THE PUBLIC HEALTH CENTER AREA MANDIRAJA I DISTRICT BANJARNEGARA - Pramudipta Fajar Sulaiman; Sudiarto; Wiwik Priyatin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Indonesia is currently facing a double burden of diseases, namely infectious diseases and non-communicable diseases, one of which is diabetes mellitus. Diabetes mellitus is a metabolic disorder with insufficient insulin produced by the body. Objective: The purpose of this study was to carry out family nursing care with diabetes mellitus using foot exercises to reduce blood sugar levels during. Methods: The subject of this study was a patient with diabetes mellitus who focused on family nursing care foot exercises as a complementary therapy. The research was conducted in the Mandiraja 1 health center area of Banjarnegara district. This research uses descriptive methods in the form of case studies. Results: Case studies on Mr. S clients with diabetes mellitus, the results showed that foot exercises can reduce blood sugar levels during the 3 visits to do foot exercises a week. Conclusion: The conclusion of the family case of Mr. S as a patient with diabetes mellitus is that the problem is resolved as expected. After implementation for 3 visits, the evaluation results found that Mr. S family for the diagosa found. S's family for the diagosa found.